(untitled) (Revista Cocar, 2019)
The stability (or not) of matter geometry in primary education Paraense in decade of (1899 - 1930) Resumo A escrita deste artigo desenvolveu-se de forma a responder à questão norteadora: Há um padrão de recorrência dos saberes geométricos nos programas de ensino de Geometria destinados ao curso primário paraense entre 1899 e 1930? A ocorrência de tal padrão pode caracterizar a estabilidade de uma matéria escolar. Assim, consideramos como fonte de pesquisa os programas de ensino de Geometria destinados, também, aos Grupos Escolares paraenses nesse período e objetivamos averiguar se há a ocorrência do fenômeno de vulgata entre tais programas. Para alcançarmos tal objetivo e respondermos a referida questão norteadora, nossa opção teórico-metodológica pautou-se em conceitos da história das disciplinas escolares de Chervel (1990). Após nos direcionarmos aos programas de ensino destacados com o olhar viabilizado pelo referencial adotado podemos inferir que existe recorrência dos saberes geométricos nos programas de ensino de Geometria destinados ao curso primário paraense entre 1899 e 1930, formando uma vulgata que representa tais programas. Palavras-chave: Programas de ensino. Geometria. Vulgata. Abstract The writing of this article was developed in way to answer the leading question: Is there a pattern of recurrence of the geometric knowledge in the geometric teaching programs destined to the primary course of the Paraense between decade of 1899 and 1930? The occurrence of such a pattern may characterize the stability of a school matter. Thus, we consider as reference source of research the Geometry teaching programs destined, also, to the Paraense, School Groups during this period and we aim to investigate if there is the occurrence of the phenomenon of vulgata among the programs of Geometry destined to the primary course in Pará between decade of 1899 and 1930. To reach this goal and answer the referred leading question, our option theoretical-methodological was based in concepts from the history of Chervel’s (1990) school subjects. Afterwards, we directions teaching detach programs, was possible by the referential, can infer that there is a recurrence of the geometric knowledge in Geometry teaching programs destined to the primary course of the Paraense between decade of 1899 and 1930, forming a vulgata that represents such programs. Keywords: Teaching Programs. Geometry. Vulgata.